Integrative analysis of the expression profile and prognostic values of SENP gene family in hepatocellular carcinoma - Xu Zhang; Chenglei Zhao; Tianyi Liu (Discover Oncology)
Abstract Introduction Hepatocellular carcinoma (HCC) stands as the fourth leading cause of cancer-related deaths worldwide. SUMO-specific peptidases, known as SENPs, emerge as critical players, regulating tumorigenesis and progression of numerous cancer types. Despite this, the specific impact of SENPs in HCC remains unclear. Hence, our study aimed to reveal the immune and prognostic implications of SENPs in HCC. Methods The gene expression of SENP in various cancers was examined using open-access databases including TCGA, GTEx, and CPTAC. In order to investigate the prognostic potential of the SENP family, Kaplan–Meier analysis was used. To clarify the underlying biological mechanisms, gene set enrichment analysis (GSEA) was carried out. cBioPortal database was used to evaluate genetic mutation profiles. For insight into the relationship between SENP genes and tumor immunity, various algorithms were used. Results Our findings showed that SENP1, SENP2, SENP3, SENP5, SENP6, and SENP7 expression levels were significantly higher in HCC tumor tissues compared to normal tissues. In HCC patients, elevated SENP1 and SENP5 expression has been associated with tumor development and poor outcomes. Our immune infiltration patterns results also showed significant correlations between SENP5 expression and neutrophil (cor = 0.346, p < 0.001), myeloid dendritic cell (cor = 0.491, p < 0.001), macrophage (cor = 0.465, p < 0.001), and memory B cell (cor = 0.336, p < 0.001) infiltration in HCC, whereas SENP1 expression was associated with none of these infiltrations. Conclusions The prognostic and immunogenetic value of SENP1 and SENP5 in HCC was demonstrated in this study. Therefore, these two genes have the potential to function as separate prognostic biomarkers and offer promise as immunotherapeutic targets in the fight against HCC.